CHARACTERIZATION OF THE GRAINS IN 2014 ALUMINIUM ALLOY AFTER EQUAL CHANNEL ANGULAR EXTRUSION (ECAE) PROCESS - Boczkal, Sonia; Lech-Grega, Marzena; Szymański, Wojciech (Image Analysis and Stereology, 2011)
In 2014 alloy deformed by Equal Channel Angular Extrusion process (ECAE) the changes in the size and shape of structural constituents were examined. The samples subjected after deformation to additional annealing at 300°C/10min were characterized by larger grains of nearly-equiaxial shapes. The microstructure after deformation was composed of a large number of the mutually crossing bands and microbands. The intersection of microbands resulted in formation of rectangular and rhombohedral grains. It was noted that the average grain size after ε = 4.6 (4 passes) was 0.2 μm.